Você está na página 1de 2

EJERCICIO PARA CLASE

Ecuaciones del sistema


𝑚1 ∗ 𝑣1ሶ 𝑡 + 𝑏1 𝑣1 𝑡 + 𝑏2 𝑣1 𝑡 − 𝑣2 𝑡 =𝑓 𝑡

𝑚2 ∗ 𝑣2ሶ 𝑡 + 𝑘 න 𝑣2 𝑡 𝑑𝑡 + 𝑏2 𝑣2 𝑡 − 𝑣1 𝑡 =0

Aplicando transformada
𝑚1 ∗ 𝑠𝑉1 𝑠 + 𝑏1 𝑉1 𝑠 + 𝑏2 𝑉1 𝑠 − 𝑉2 𝑠 =𝐹 𝑠
𝑘
𝑚2 ∗ 𝑠𝑉2 𝑠 + 𝑠 𝑉2 𝑠 + 𝑏2 𝑉2 𝑠 − 𝑉1 𝑠 =0

Ordenando
𝑉1 𝑠 𝑚1 ∗ 𝑠 + 𝑏1 + 𝑏2 − 𝑉2 𝑠 𝑏2 = 𝐹 𝑠
𝑘
𝑉2 𝑠 𝑚2 ∗ 𝑠 + + 𝑏2 − 𝑉1 𝑠 𝑏2 = 0
𝑠
Eliminando 𝑽𝟏 𝒔
𝑘
𝐹 𝑠 + 𝑉2 𝑠 𝑏2 𝑉2 𝑠 𝑚2 ∗ 𝑠 + 𝑠 + 𝑏2
=
𝑚1 ∗ 𝑠 + 𝑏1 + 𝑏2 𝑏2
𝑘
𝐹 𝑠 𝑏2 + 𝑉2 𝑠 𝑏2 2 = 𝑉2 𝑠 𝑚2 ∗ 𝑠 + + 𝑏2 𝑚1 ∗ 𝑠 + 𝑏1 + 𝑏2
𝑠
𝑘
𝐹 𝑠 𝑏2 = 𝑉2 𝑠 𝑚2 ∗ 𝑠 + + 𝑏2 𝑚1 ∗ 𝑠 + 𝑏1 + 𝑏2 − 𝑏2 2
𝑠
𝑉2 𝑠 𝑏2
= 𝐺2 𝑠 =
𝐹 𝑠 𝑘
𝑚2 ∗ 𝑠 + 𝑠 + 𝑏2 𝑚1 ∗ 𝑠 + 𝑏1 + 𝑏2 − 𝑏2 2
𝑉2 𝑠 𝑏2
= 𝐺2 𝑠 =
𝐹 𝑠 1
𝑠 2 𝑚1 𝑚2 + 𝑠 𝑚2 𝑏1 +𝑚2 𝑏2 +𝑚1 𝑏2 + 𝑠 𝑏1 𝑘 + 𝑏2 𝑘 + 𝑚1 𝑘 +𝑏1 𝑏2
Eliminando 𝑽𝟐 𝒔
𝑉1 𝑠 𝑚1 ∗ 𝑠 + 𝑏1 + 𝑏2 − 𝐹 𝑠 𝑉1 𝑠 𝑏2
=
𝑏2 𝑘
𝑚2 ∗ 𝑠 + 𝑠 + 𝑏2
𝑘
𝑉1 𝑠 𝑚1 ∗ 𝑠 + 𝑏1 + 𝑏2 − 𝐹 𝑠 𝑚2 ∗ 𝑠 + + 𝑏2 = 𝑉1 𝑠 𝑏2 2
𝑠
𝑘 𝑘
𝑉1 𝑠 𝑚1 ∗ 𝑠 + 𝑏1 + 𝑏2 𝑚2 ∗ 𝑠 + + 𝑏2 − 𝑏2 2 = 𝐹 𝑠 𝑚2 ∗ 𝑠 + + 𝑏2
𝑠 𝑠
𝑘
𝑉1 𝑠 𝑚2 ∗ 𝑠 + 𝑠 + 𝑏2
= 𝐺1 𝑠 =
𝐹 𝑠 𝑘
𝑚1 ∗ 𝑠 + 𝑏1 + 𝑏2 𝑚2 ∗ 𝑠 + 𝑠 + 𝑏2 − 𝑏2 2
𝑘
𝑉1 𝑠 𝑚2 ∗ 𝑠 + 𝑠 + 𝑏2
= 𝐺1 𝑠 =
𝐹 𝑠 1
𝑠 2 𝑚1 𝑚2 + 𝑠 𝑚2 𝑏1 +𝑚2 𝑏2 +𝑚1 𝑏2 + 𝑠 𝑏1 𝑘 + 𝑏2 𝑘 + 𝑚1 𝑘 +𝑏1 𝑏2